2015
DOI: 10.1038/nrendo.2015.117
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and pathophysiological roles of NAMPT and NAD metabolism

Abstract: Nicotinamide phosphoribosyltransferase (NAMPT) is a regulator of the intracellular nicotinamide adenine dinucleotide (NAD) pool. NAD is an essential coenzyme involved in cellular redox reactions and is a substrate for NAD-dependent enzymes. In various metabolic disorders and during ageing, levels of NAD are decreased. Through its NAD-biosynthetic activity, NAMPT influences the activity of NAD-dependent enzymes, thereby regulating cellular metabolism. In addition to its enzymatic function, extracellular NAMPT (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
470
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 531 publications
(509 citation statements)
references
References 186 publications
(212 reference statements)
9
470
1
5
Order By: Relevance
“…NAMPT is expressed at high levels in several different cancers and, therefore, this enzyme has been considered a potential therapeutic cancer target (5,9,27). Recent studies in glioblastoma have indicated specific genetic subgroups may be exquisitely sensitive to NAMPT inhibition (28,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NAMPT is expressed at high levels in several different cancers and, therefore, this enzyme has been considered a potential therapeutic cancer target (5,9,27). Recent studies in glioblastoma have indicated specific genetic subgroups may be exquisitely sensitive to NAMPT inhibition (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…The failure of these interventions to generate a durable response stems in part from inadequate understanding of the metabolic and molecular mechanisms underlying malignant behavior and therapeutic resistance (3,4). Nicotinamide adenine dinucleotide (NAD + ) has a well-known role in cellular metabolism and is an important cofactor for signaling pathways that regulate aging, inflammation, diabetes mellitus, axonal injury, and cancer (5,6). Nicotinamide phosphoribosyltransferase (NAMPT), the rate-limiting enzyme in mammalian NAD + synthesis, produces NAD + precursor nicotinamide mononucleotide (NMN) to drive NAD + -dependent processes.…”
mentioning
confidence: 99%
“…For a review of the many apparent functions of human nicotinamide phosphoribosyltransferase, consult the article by Garten and colleagues (269). It is unclear if the many functions may be ascribed simply to variations in the NAD pool.…”
Section: Reactions At the Anomeric Carbon Of Prppmentioning
confidence: 99%
“…Recently, several lines of evidence have implicated the critical roles of NAD in a broad range of biological functions. NAD participates in the transduction of numerous important intracellular signalling pathways and controls cell proliferation, death, metabolism, circadian rhythms and ageing (Garten et al, 2015;. The effects of NAD on a group of NAD-dependent proteins, such as the sirtuin family of proteins and PARP1, are the main mechanisms behind NAD's biological functions (Garten et al, 2015;Zhang et al, 2016;Jokinen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%